A marginal majority: women, gender, and a reimagining of Southern Baptists - Flowers, Elizabeth H.; Seat, Karen K. (America's Baptists, 2020)
"A greater influence than you imagine" : women lead the way to Southern Baptist centralization / C. Delane Tew -- "A Christian attitude toward other races" : Southern Baptist women and race relations, 1945-1965 / Melody Maxwell -- From Molly Marshall to Sarah Palin : Southern Baptist gender battles and the politics of complementarianism / Karen K. Seat.